2005
DOI: 10.1186/gb-2005-6-12-r101
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A Populus euphratica DNA microarray was constructed and used to analyze gene expression in trees growing in the desert. P. euphratica is shown to express a set of genes that is different from other Populus trees and these genes contribute to adaptation to saline growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(57 citation statements)
references
References 54 publications
4
53
0
Order By: Relevance
“…Sugar plays important roles as an osmoprotectant and as an immediate energy source in plants (Wingler and Roitsch, 2008). Many studies have reported increased sugar contents in plants under salt stress (Brosché et al, 2005;Gong et al, 2005;Sanchez et al, 2008;Li et al, 2016;Luo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar plays important roles as an osmoprotectant and as an immediate energy source in plants (Wingler and Roitsch, 2008). Many studies have reported increased sugar contents in plants under salt stress (Brosché et al, 2005;Gong et al, 2005;Sanchez et al, 2008;Li et al, 2016;Luo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Populus euphratica has a particularly high scientific interest due to its high salt, heat and drought tolerance, having been increasingly used for studies in tree molecular biology and biotechnology (Ma et al 1997;Chen et al 2001;Gries et al 2003;Gu et al 2004a;Brosche et al 2005;Ferreira et al 2006). This poplar species is tolerant to poor soils, high salinity and to extreme temperatures (Fu and Chin 1992;Gu et al 1999b;Gu et al 2004a;Gu et al 2004b;Ferreira et al 2006) and it is considered a phreatophyte (Gries et al 2003), being highly sensitive to hydraulic dysfunctions in the xylem (Hukin et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…To elucidate the functions of CBL gene members respectively in regulating plant response to external stimuli, we also isolated and characterized nine of the CBL genes members from Populus euphratica, a pioneer tree species distributing in desert regions of China and many Middle Eastern countries. It exhibits high tolerance to salinity and drought stresses, making it a valuable plant species for the study of physiological and molecular mechanism underlying woody plants adaptation to environmental stresses (Gu et al 2004;Brosché et al 2005;Ottow et al 2005). For a successful stress defense, Populus euphratica must have developed a network of signal transduction pathways to cope with environmental stresses.…”
Section: Introductionmentioning
confidence: 99%